2000
DOI: 10.1590/s0104-14282000000400006
|View full text |Cite
|
Sign up to set email alerts
|

Síntese e caracterização de poliuretanos segmentados contendo blocos de peso molecular controlado. Parte 2: correlações entre morfologia e comportamentos térmico e mecânico

Abstract: Poliuretanos segmentados formados por segmentos flexíveis e rígidos bem caracterizados foram sintetizados através de uma nova metodologia de síntese, em que cada segmento foi preparado separadamente, e ambos acoplados em uma etapa posterior (produtos SPU). Uma outra série de poliuretanos segmentados similares em composição foi obtida pelo método tradicional em duas etapas (produtos PU). As propriedades térmicas e mecânicas destes materiais foram determinadas por calorimetria diferencial de varredura e ensaios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…15 According to Hourston et al 16 the T g of the hard segment is expected at about 808C, however the detection using DSC is not always possible. 17 One reason for this lack of signal is the low sensitivity of DSC analysis for detecting second order transitions; more sensitivity methods like dynamic mechanical thermal analysis are required. 16 Brown et al 4 and Kukanja et al 18 have also reported the lack of a clear transition in PU/acrylic systems.…”
Section: Thermal Analysismentioning
confidence: 99%
“…15 According to Hourston et al 16 the T g of the hard segment is expected at about 808C, however the detection using DSC is not always possible. 17 One reason for this lack of signal is the low sensitivity of DSC analysis for detecting second order transitions; more sensitivity methods like dynamic mechanical thermal analysis are required. 16 Brown et al 4 and Kukanja et al 18 have also reported the lack of a clear transition in PU/acrylic systems.…”
Section: Thermal Analysismentioning
confidence: 99%
“…Pitera [22] studied the effect of increasing polyol chain length on TDI-cured polyoxyethyleneglycols; the heat effect of endothermic processes within 260-420°C becomes lower and lower, while the effect at 360-440°C becomes more important. They correlated this effect with the increasing share of ether-type bonds or estertype bonds with simultaneous reduction in the number of urethane groups; polyether PUs from polypropylenglycol (PPG), HDI, and BDO had melting temperatures of 223°C [23]. These few examples are representative of the general trend that polyester polyol-based PUs are more thermally stable than polyether macrodiol-based PUs.…”
Section: And Pilchmentioning
confidence: 96%